Mothers' knowledge and management of fever in febrile children - Yasemin Korkut (SERNEV, 2018)
Introduction: This studywas planned to determine the knowledge, thoughts, and attitudes of mothers with0-7-years-old children and related factors about fever.Methods: The study was conductedwith 112 mothers who applied to the Dumlupınar University Evliya ÇelebiHospital Family Practice Policlinics. The data were collected by aquestionnaire consisting of multiple-choice questions.Results: The mean age of themothers was 31 ± 5.3 years. According to the educational status, 68 (60.7%)were primary school graduates, 30 (26.7%) were high school graduates, and 14(12.5%) were university graduates. The mean number of children was 3 ± 1.7. Ofthe parents surveyed, 65% stated that they owned a thermometer, but still 53(47.3%) mothers were evaluating the child's fever by touching and 13 by lookingat the general appearance. ‎Thirty-three (29.4%) mothers were usingthermometers to measure fever. Although 75 (67%) mothers claimed to knowhow tomeasure body temperature, only 18 (16%) were able to describe how to make acomplete and accurate measurement. Of the mothers who said they knew how to usea thermometer, 17 (22.6%) guessed the required duration for measurement lessand 29(38.6%) unnecessarily higher than needed. Eighty-eight (78.5%) of themothers measured the body temperature from the axillary region, followed bytympanic, oral, and in small children rectal routes.Conclusion: Mothers oftenhave false or incomplete information about the location, duration, and methodof temperature measurement.